2023
DOI: 10.3748/wjg.v29.i1.157
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound guided radiofrequency ablation for pancreatic tumors: A critical review focusing on safety, efficacy and controversies

Abstract: The role of endoscopic ultrasound (EUS) in the last two decades has shifted from a diagnostic tool to an important therapeutic tool treating mainly pancreato-biliary disorders. In recent years, its applications for treating pancreatic diseases have broadened, including the implementation of radiofrequency ablation (RFA), which has been traditionally used for treating solid tumors. In this critical in-depth review, we summarized all the papers throughout the literature regarding EUS-RFA for pancreatic neuroendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Our data were compatible with a recent review article that showed a technical success of 100%, and complete radiological success of 90%. 28 Moreover, the clinical success rate in our study, especially in patients with F-pNENs, was high, 94.9% (95% CI 90.7-97.9%). To date, only few systematic reviews and meta-analyses assessing EUS-RFA for pNENs with a relatively low number of patients were published.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Our data were compatible with a recent review article that showed a technical success of 100%, and complete radiological success of 90%. 28 Moreover, the clinical success rate in our study, especially in patients with F-pNENs, was high, 94.9% (95% CI 90.7-97.9%). To date, only few systematic reviews and meta-analyses assessing EUS-RFA for pNENs with a relatively low number of patients were published.…”
Section: Discussionmentioning
confidence: 44%
“…Similarly, the complete radiological response was high in 87.1% (95% CI 80.1–92.8%). Our data were compatible with a recent review article that showed a technical success of 100%, and complete radiological success of 90% 28 . Moreover, the clinical success rate in our study, especially in patients with F‐pNENs, was high, 94.9% (95% CI 90.7–97.9%).…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of observation is the avoidance of the morbidity and mortality associated with pancreatic resection[ 91 ]. With advancements in interdisciplinary approaches, EUS-guided RFA (EUS-RFA) has emerged as a potential treatment option for pancreatic tumors[ 92 ]. In a study by Choi et al [ 93 ], two patients with SPTP underwent EUS-RFA without experiencing any procedure-related adverse events, and one patient achieved a complete response.…”
Section: Treatment Approachesmentioning
confidence: 99%
“…[36][37][38] Acute pancreatitis is a known AE after ERCP but also after endoscopic ultrasound-guided radiofrequency ablation of pancreatic lesions and even after antegrade device-assisted enteroscopy. [37][38][39][40][41] Splenic injury is a rare AE related to a difficult colonoscopy. 42 Postpolypectomy coagulation syndrome with localized peritonitis is related to endoscopic resection techniques in the colon using coagulation, and even coagulation-induced gas explosion with colonic perforation has been described after incomplete bowel preparation.…”
Section: Type Of Ae According To Endoscopic Proceduresmentioning
confidence: 99%
“…Retained food during upper gastrointestinal endoscopy is a risk factor for aspiration pneumonia 36–38 . Acute pancreatitis is a known AE after ERCP but also after endoscopic ultrasound‐guided radiofrequency ablation of pancreatic lesions and even after antegrade device‐assisted enteroscopy 37–41 . Splenic injury is a rare AE related to a difficult colonoscopy 42 .…”
Section: Type Of Ae According To Endoscopic Proceduresmentioning
confidence: 99%